Effects of pollen patties with curcumin-steviol glycoside complex on Apis mellifera - Sehyun Park; Jihwan Lee; Gyutae Park; Dongcheol Song; Seyeon Chang; Jaewoo An; Kyeongho Jeon; Hyuck Kim; Youngho Lim; Jaeyoung Kim; Kisu Ahn; Jungseok Choi; et al. (Journal of Animal Science and Technology)
The main objective of this study was to investigate the effects of pollen patty with supplementation of different concentrations of curcumin-steviol glycoside complex (CSG) in Apis mellifera (A. mellifera). Twelve colonies of A. mellifera were conducted from July 10th to August 21st for 42 days. A. mellifera were assigned to four dietary treatments with 3 replicates of equal size as follows: no supplementation of pollen patty (NC), supplementation of basal pollen patty (PC), supplementation of basal pollen diets + 0.04% of CSG (T1), supplementation of basal pollen diets + 0.08% of CSG (T2). The percentage of CSG was calculated based on the total weight of pollen patties. Thorax weight was significantly increased (p < 0.05) in the T2 diet compared with the NC and PC diet. There was no significant difference (p > 0.05) in pollen patties consumption among the PC, T1, and T2 diets. The T1 and T2 diets showed significantly higher (p < 0.05) honey production than the PC and NC diets. Also, the PC diet showed significantly higher (p < 0.05) honey production than the NC diet. The T2 showed significantly higher (p < 0.05) brood area than the PC and NC diets at 28 and 42 days. In addition, the PC and T1 diets showed significantly higher (p < 0.05) brood areas than the NC diet. The T1 and T2 diets showed significantly higher (p < 0.05) catalase and superoxide dismutase (SOD) 1 gene expression than the PC and NC diets. The expression of the thioredoxin reductase (Trxr) 1 gene was significantly higher (p < 0.05) in the T1 diet, and decreased in the order of the PC, T2, and NC diets. The expression of the SOD2 gene was significantly higher (p < 0.05) in the T1 diet than the PC and T2 diets and was significantly lower (p < 0.05) in the NC diet. Therefore, supplementation of CSG to pollen patty might be the ideal strategy to improve A. mellifera performances.